Motor controlled system development with force-assistance using force/torque sensor for four-axis ceiling suspension system - Kshitij Ghanshyam Jiwane; Sudhir Madhav Patil; Maneetkumar R. Dhanvijay (International Journal of Power Electronics and Drive Systems (IJPEDS), 2023)
Multi-axis force and torque sensors are type of transducers. They can measure force and torque in three dimensions. These sensors have multiple applications in robotic systems. The majority of these type of sensors use the strain measurement in any elastic structure. There are multiple approaches for strain measurement which include resistive strain gauge, piezo-electric and capacitive technologies. The evaluation of such a system can be done on various parameters, maximizing the acceptable sensing range while minimizing measurement errors/crosstalk is the main design challenge. In future, because force and torque sensors are necessary for service machines to interact with people in different situations, they will be widely deployed. However, it is challenging to find an appropriate force/torque sensor, and the cost is very high, because of certain design concerns and needs. This paper discusses an application based on the multi-axis force/torque sensor. A force-assisted control system has been proposed with simultaneous motorized action using force as feedback. The sensor needs and machine performance are reviewed after a thorough analysis of relevant data. This thorough investigation will benefit in the interfacing of specialized force/torque sensors to reduce crosstalk and aid in broadening the scope of service machines in which they can be used.